ANALISIS PENGAWASAN PETUGAS AVIATION SECURITY (AVSEC) DALAM MENDETEKSI BAHAN PELEDAK DI BANDAR UDARA KOMODO LABUAN BAJO - Asri; Elnia Frisnawati (Transpublika Publisher, 2022)
Aviation Security (AVSEC) officer still frequently discover dangerous goods in passenger luggage, such as scissors, knives, small gas cylinders, machetes/swords, razors, gas lighters, cutlery, a power bank that exceeds the limit, sea shells, pink sand, and marine life in the Prohibited Item category. Researchers also discovered that many passengers were bringing alcoholic beverages that were not labeled and exceeded the specified standards. This research aims 1) To discover how Aviation Security (AVSEC) officers play a part to aviation security and safety at Komodo Labuan Bajo Airport. 2) To determine what equipment is required to support Security Check Point (SCP) two in maintaining aviation security and safety at Komodo Labuan Bajo Airport. 3) To find out how Komodo Labuan Bajo Airport Aviation Security (AVSEC) officers handle dangerous explosive materials. This research uses qualitative methods. Data collection is carried out by observation methods, interviews, and documentation which are then carried out data analysis using data reduction, data presentation and conclusions. The results of this study reveal that 1) Aviation Security Officers (AVSEC) have a very important role in ensuring flight security and safety, 2) Passenger inspections on SCP 2 are carried out Security checks on SCP 2 must be supported by inspections with flight security aids, where inspections This is done by using X-Ray machine tools, Walk Through Metal Detector (WTMD), and Hand Hel Metal Detector (HHMD), 3) Aviation Security Officers (AVSEC) in handling explosives that are considered dangerous to all parties must carry out regular inspections. strict restrictions on passengers and goods that enter the area at Komodo Labuan Bajo Airport to prevent the transportation of prohibited and dangerous goods and can be used to threaten safety and security.